2017
DOI: 10.5606/tftrd.2017.311
|View full text |Cite
|
Sign up to set email alerts
|

Lumbrical-interosseous recording technique versus routine electrodiagnostic methods in the diagnosis of carpal tunnel syndrome

Abstract: Objectives:We aimed to evaluate the sensitivity of second lumbrical-interosseous (L-I) technique and to compare the results with other electrophysiological methods in patients with carpal tunnel syndrome (CTS). Patients and methods:This cross-sectional study was conducted in an electrophysiology laboratory of a university hospital between January 2003 and January 2004. A total of 102 patients with CTS (174 hands) and 40 healthy controls (80 hands) were included. Median motor nerve conduction studies were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
4
2
0
Order By: Relevance
“…This larger proportion of female patients compared to male patients is similar to that in previous studies [ 1 , 12 , 13 ] and may be caused by a combination of factors such as hormonal changes in women and performing more housework in the family. Consistent with previous findings [ 12 , 14 , 15 ], bilateral incidence had the highest occurrence (82%) among patients, and the number of patients with CTS on the right hand was higher than those with the disorder on the left hand. The greater incidence on the right side may be because most people are right-handed and perform more repetitive movements using the right hand than the left hand.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This larger proportion of female patients compared to male patients is similar to that in previous studies [ 1 , 12 , 13 ] and may be caused by a combination of factors such as hormonal changes in women and performing more housework in the family. Consistent with previous findings [ 12 , 14 , 15 ], bilateral incidence had the highest occurrence (82%) among patients, and the number of patients with CTS on the right hand was higher than those with the disorder on the left hand. The greater incidence on the right side may be because most people are right-handed and perform more repetitive movements using the right hand than the left hand.…”
Section: Discussionsupporting
confidence: 92%
“…A simple increase in MSDL does not indicate that CTS should be diagnosed, but a comparison with the UN on the same hand and MUD calculation can provide better insight regarding the problem. Most of the previously reported MSDL cut-off values were between 2.7 and 3.8 ms (mostly around 3.7 ms), with a sensitivity of 67% ~ 90% and a specificity mostly above 90% [ 3 , 14 , 15 , 21 , 23 26 ]. In our study, the sensitivity of MSDL for the diagnosis of CTS was 92.2% and the specificity was 99.4%, which were similar to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the small latency differences in our results. This was in concordance with Yılmaz et al [28], as in their CTS group, the mean difference was found to be (1.40 ms), whereas it was (0.12ms) in the control group, indicating a significant difference between the two groups (p < 0.001). The previous study was also in agreement with findings of Ozben et al ( 2012 In the present study, we used the 7-joint US score as it combines soft tissue changes (synovitis and tenosynovitis) by gray scale (GS) and neovascularization by Power Doppler (PD) in addition to erosive bony changes and it reveals clinical correlation with diseases activity as well [21].…”
Section: Discussionsupporting
confidence: 92%
“…The simple prolongation of MSDL does not indicate that CTS can be diagnosed, but comparing with its own UN and calculating MUD can explain the problem better. Most of the previously reported MSDL cut-off values were between 2.7-3.8 ms, and more were around 3.7 ms, the sensitivity is 67%~90%, and the speci city is mostly greater than 90% (3,11,12,18,(20)(21)(22)(23). In our study, the sensitivity of MSDL to diagnose CTS was 85.5%, and the speci city was 90.4%, which was similar to the results of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…The higher incidence of women may be caused by a combination of factors such as women taking on more housework in the family and changes in the hormone levels in women. Among the types of patients, bilateral incidence is the most (82%), and the number of patients on the right side is more than that on the left side, which is consistent with previous studies (9,11,12). The greater incidence on the right side than on the left may be due to the fact that the majority of people are right-handed and have more repetitive movements than left.…”
Section: Discussionsupporting
confidence: 89%